Pemberdayaan Kader Melalui Optimalisasi dan Pembuatan Cookies Tepung Kelor dengan Penambahan Tepung Ubi Banggai dan Tepung Kedelai Sebagai Upaya Peningkatan Gizi ddan Penurunan Stunting di Kabupaten Donggala - Nurasmi, Nurasmi; Irnawati, Irnawati; Kariani, Ni Ketut (Abdimas Indonesian Journal, 2025)
Stunting is a condition of impaired growth and development in children caused by chronic malnutrition and recurrent infections. Posyandu cadres, as community health representatives, play a critical role in providing health education, delivering basic services, expanding healthcare access in remote areas, and raising public awareness of healthy lifestyles. Strengthening their knowledge and skills is therefore essential. This program aimed to enhance cadres’ competencies in producing cookies made from Moringa oleifera flour, Banggai sweet potato flour, and soybean flour. The implementation comprised several stages: situational analysis with community partners, obtaining authorization from local government, preparing tools and materials, conducting socialization activities, delivering cadre education and training sessions, followed by monitoring and evaluation. Pre-test results revealed low baseline knowledge, categorized as poor (5%), fair (70%), and good (25%). After the intervention, knowledge improved significantly to poor (0%), fair (15%), and good (85%), indicating a 60% overall increase. In addition, cadres gained practical skills in processing moringa, Banggai sweet potato, and soybean flours, as well as developing cookies derived from these local ingredients. In conclusion, the training program substantially improved cadres’ knowledge and practical skills, particularly in formulating innovative supplementary foods based on local food resources, thereby supporting community-based efforts to prevent stunting.